Infiltration Rate at Several Land Cover in Sangkulirang-Mangkalihat Karst Area of East Kutai Regency. - Sri Sarminah, Indirwan . (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2017)
This study aims to determine the rate of infiltration in some land cover and soil physical properties in Sangkulirang-Mangkalihat Karst Area in Sekerat Village, Bengalon, East Kutai Regency. Infiltration rate measurements were made using Double Ring Infiltrometer with three repetitions at several land cover ie semak belukar, secondary forest and Karst area. Soil physical analysis includes bulk density, total pores,soil moisture content, soil texture and soil structure. The results showed that the average infiltration rate of 724.44 mm / hour (Very Fast), secondary forest 259.88 mm / hour (Very Fast) and karst land of 93.07 mm / hour (Fast ). The result of laboratory analysis of soil physical characteristic that is bulk density is 1.07 g / cm3, total pores 39.65%, soil moisture content 3,112%, sand soil texture and single grain ground structure; secondary forest obtained bulk density 1.26 gr / cm3, total pores 34.63%, soil moisture content 11.994%, clay soil texture and granular soil structure and in karst land obtained bulk density 1.27 gr / cm3, total pore 34, 27%, soil moisture content 18.457%, clay soil texture and granular soil structure.